Experimental and Numerical Analysis of the Performance of Various Damper Materials - Premnath, Mithun; Gopi, Kriparaj Kareveliparambil (Trends in Sciences, 2023)
The vibration in ships causes structural fatigue, damage to electrical and mechanical devices, excessive level of noise and discomfort to the passengers and crews. Sometimes the increase in ship vibration leads to unsafe operating conditions and thereby discarding it. Thus, the research on vibration reduction is essential in the maritime field and this paper deals with the reduction of vibrations in marine machinery using elastomeric bearings. The numerical analysis of the performance of passive vibration isolators with different damping materials was conducted using ANSYS and the results are validated experimentally. With the help of a vibration exciter, vibration transmissibility at different frequencies is plotted and the hysteresis curve was generated numerically by applying a cyclic load to the bearing. Then, the best damping material was deducted by comparing the calculated loss factor of different elastomeric materials such as natural rubber, styrene-butadiene rubber and polybutadiene Rubber (PBR) and their combinations. The natural rubber blended with styrene-butadiene rubber (SBR) and polybutadiene rubber (PBR) shows an increase in the damping property of the elastomer and can be used for high-frequency damping applications. HIGHLIGHTS Study of damping property of various elastomers. Experimental as well as numerical analysis were done to find the loss factor of elastomers The transmissibility curve of the elastomers was plotted at different frequencies ranging from 10 - 4000 Hz using a vibration exciter and the loss factor was calculated using half power band width method Hysteresis curve of elastomers were generated numerically using ANSYS software and the loss factor of the elastomers was calculated theoretically GRAPHICAL ABSTRACT